'Bioexit': navigating the policy and regulatory pathways for the biotechnology industry in a post-Brexit landscape. Issue 7 (July 2018) - Mackey, Tim K.; Annaloro, John
Highlights: Brexit is a destabilizing with short and long-term implications for biotechnology. Four existing post-Brexit pathways fail to protect the UK–EU biotechnology sector. An alternative pathway is needed to ensure regulatory synergy and patient safety. We outline policy mechanisms to ensure regulatory continuity post-Brexit. Abstract : The withdrawal of the UK from the European Union (EU) is a complicated event. Although implications vary by industry, the biotechnology sector is especially vulnerable to the consequences of Brexit. Accordingly, here we evaluate potential repercussions under four post-Brexit political pathways: European Economic Area (EEA) affiliation (Norwegian Model); negotiated bilateral access (Swiss Model); limited participation in EU Customs Union (Turkish Model); or independence under the World Trade Organization (WTO) designation. We conclude that all four pathways fail to protect the mutually beneficial UK–EU biotechnology relationship and that alternative pathways need to be explored. Accordingly, we outline a suite of policy mechanisms aimed at ensuring continued EU–UK regulatory synergy, with the central aim of ensuring access to biomedical innovations and ensuring patient safety.